2020
DOI: 10.56890/jpacd.v21i.7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of fermented cactus pear (Opuntia spp.) and its effect on liveweight gain of Dorper lambs

Abstract: The high-water (85%) and low protein (5%) content of cactus cladodes (Opuntia spp.) reduce the amount of dry-matter consumed by ruminants. The objective of this study was to use protein enrichment technology to increase Opuntia protein content and to feed Dorper lambs, comparing the Opuntia protein enrichment and the basal diet in the liveweight gain. The experiment was carried out for 60 days, using a biodigester (100 kg of cactus) -Title No. 2641- IMPI. The process was based on the daily aerobic semisolid fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…This recycling consisted of reutilizing the previously fermented juice, which allowed a considerable saving in the process since the cost of dry yeast was approximately 5.00 USD for each 100 kg of cladodes. Previous studies (Flores-Hernández et al, 2017a,b, 2019 have demonstrated that using "new" yeast weekly did not have a significant effect in the fermentation process.…”
Section: Proximal Analysis: Non-fermented and Fermented Cladodesmentioning
confidence: 91%
See 1 more Smart Citation
“…This recycling consisted of reutilizing the previously fermented juice, which allowed a considerable saving in the process since the cost of dry yeast was approximately 5.00 USD for each 100 kg of cladodes. Previous studies (Flores-Hernández et al, 2017a,b, 2019 have demonstrated that using "new" yeast weekly did not have a significant effect in the fermentation process.…”
Section: Proximal Analysis: Non-fermented and Fermented Cladodesmentioning
confidence: 91%
“…This equipment showed advantages because all the process was mechanically performed, consequently, saved time and labor; additionally, a unicellular fungus (Sacharomyces cereviceae) and two nitrogenous sources, urea and ammonium sulfate were used as nutrients (Flores-Hernández et al, 2017a). The fermented prickly pear of different cultivars and varieties -applying the described technology-has been used to feed goats and assess consumption and weight gain (Flores-Hernández et al, 2017b), as well as in sheep to assess daily, weekly, and monthly weight gain (Flores-Hernández et al, 2019). Therefore, the objectives of this study were to assess bimonthly production of cladodes of the var.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that evaluated the effect of fresh nopal intake on the regulation of insulin resistance in sows during the lactation phase, a reduction in the levels of blood glucose and an increase in feed consumption were observed, followed by a positive impact on the sow's reproductive performance (Ordaz-Ochoa et al, 2017). In ruminants, the consumption of nopal improves milk production and bacteriological quality, body weight, and meat quality (Urrutia et al, 2014;Pérez-Sánchez et al, 2015;Flores-Hernández et al, 2019). Despite these benefits, fresh nopal, once harvested, has a limited shelf life due to its high-water content.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos investigadores (Flores Hernández et al, 2019;Herrera Torres et al, 2014;Meza Herrera et al, 2019) han llevado a cabo la FES con algunos cultivos de levaduras para incrementar el contenido de proteína cruda de nopal cultivado, el cual ha sido mejorado genéticamente para que no tenga espinas. Sin embargo, no existen trabajos que evalúen la calidad nutritiva y el desarrollo microbiano en especies de nopal silvestre, las cuales se caracterizan por tener abundantes espinas y requieren de ser eliminadas antes de ofrecer este forraje al ganado.…”
Section: Introductionunclassified